2021
DOI: 10.1159/000518873
|View full text |Cite
|
Sign up to set email alerts
|

NETest: A Systematic Review Focusing on the Prognostic and Predictive Role

Abstract: The NETest is a standardized and reproducible liquid biopsy for neuroendocrine tumors (NETs). It evaluates the expression of 51 NET genes by real-time polymerase chain reaction, providing an accurate molecular profile of the neoplasm. Diagnostic utility of NETest has been widely demonstrated, while its role in predicting prognosis and treatment response is less studied. This systematic review aims to collect and discuss the available evidence on the prognostic and predictive role of NETest, trying to answer 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…Samples that exhibit lower tumor activity strongly indicate indolent tumor behavior. These metrics are in line with our and other previous cross-sectional studies, but the reproducibility of NETest scores in individuals has not been studied before since long-term data on repeated NETest samples (>1 year) were missing ( 19 , 22 , 23 , 24 ). AUROC analysis of consecutive samples showed a shift in test accuracy during years of disease evolution and a decrease in predictive value, putting the NETest role as follow-up marker into a new perspective.…”
Section: Discussionsupporting
confidence: 91%
“…Samples that exhibit lower tumor activity strongly indicate indolent tumor behavior. These metrics are in line with our and other previous cross-sectional studies, but the reproducibility of NETest scores in individuals has not been studied before since long-term data on repeated NETest samples (>1 year) were missing ( 19 , 22 , 23 , 24 ). AUROC analysis of consecutive samples showed a shift in test accuracy during years of disease evolution and a decrease in predictive value, putting the NETest role as follow-up marker into a new perspective.…”
Section: Discussionsupporting
confidence: 91%
“…In the field of biochemical markers, growing attention is paid to NETest, an application of liquid biopsy in the field of NET, which has also demonstrated a prognostic role ( 36 ). In a larger study on the personalized approach to patients affected by neuroendocrine neoplasms, Frilling et al.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of 51 related genes is analyzed by the use of a real‐time polymerase chain reaction. This recently developed test is superior to chromogranin A 29 . Pęczkowska et al demonstrated its diagnostic value also in PCCs/PGLs 30 …”
Section: Symptoms and Diagnostic Laboratorymentioning
confidence: 99%